PERAN GURU PAI DALAM MENGINTEGRASIKAN BUDAYA RELIGIUS KE DALAM AKHLAK SISWA - Romenah Romenah; Yunus Yunus (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the phenomenon of moral decadence and the challenges of globalization that demand strengthening of students' character through religious education. The purpose of this research is to analyze the strategy and effectiveness of the role of Islamic Religious Education (PAI) Teachers in integrating religious culture as an instrument for developing students' morals. This research uses a descriptive qualitative approach. Data were collected through participant observation, documentation studies, and in-depth interviews with 22 informants consisting of school principals, teachers, students, parents, and alumni. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions according to the interactive model of Miles and Huberman. The results of the study indicate that: (1) The strategy of Islamic Religious Education (PAI) Teachers is carried out through the creation of a religious school ecosystem (school culture) as a hidden curriculum through tadarus activities, congregational prayers, and Al-Qur'an literacy; (2) The effectiveness of moral development is highly dependent on the role of Islamic Religious Education (PAI) Teachers as uswah hasanah (life role models) and humanistic personal mentors; (3) Internalization of values ​​occurs through a habituation process that transforms verbalistic religious understanding into real actions; (4) Synergy between schools and parents, as well as the use of information technology, is a strategic solution to overcome the obstacle of value contamination from social media.